APLIKASI PENJADWALAN MENGGUNAKAN ALGORITMA WELCH POWELL (STUDI KASUS : SMA MUHAMMADIYAH KENDARI) - Niarma Niarma; Bambang Pramono; LM Tajidun (semanTIK, 2018)
Scheduling teaching and learning activities is a routine work performed by the Head of Curriculum Section each welcoming the new school year. The role of the Head of Curriculum Section in making the schedule of teaching and learning activities is very important and not easy because the schedule to be arranged consists of very much data. Based on the problems that exist in SMA Muhammadiyah kendari where the teacher chose the schedule of willingness to teach sendri. To assist the processing of subject schedules at SMA Muhammadiyah Kendari, it is necessary to have a scheduling information system using Welch Powell algorithm. Welch Powell algorithm is one of the methods used to solve optimization problems by performing staining based on the highest degree of Largest Degree Ordering or LDO nodes. The LDO method is considered appropriate for scheduling problems because it prioritizes the highest-level nodes that are connected by multiple patterns so they should take precedence for scheduling.By entering the necessary data, such as class data, subjects, teachers, time, school year, and willingness to teach. The system will generate lesson schedules based on teachers' willingness to teach and automatically schedule teachers who have not chosen a willingness to teach without clashing.Keywords— Welch Powell, Application, SchedulingDOI : 10.5281/zenodo.1343344